2012
DOI: 10.1080/15421406.2012.635925
|View full text |Cite
|
Sign up to set email alerts
|

Layered Double Hydroxides as Nano Additives in Poly(ϵ-caprolactone)

Abstract: Poly(ε-caprolactone) MgAl -layered double hydroxides (MgAl-LDH) nanocomposites were prepared by melt intercalation. Two organically modified MgAl-LDH, stearic acid (stearate) and sodium dodecyl sulphate (SDS), were used. Nanocomposites morphology was studied by XRD and TEM. Thermal properties were analysed by TG and DSC. Although both systems showed presence of a mixed morphology, exfoliated and intercalated, MgAl-LDH stearate nanocomposites showed a better dispersion of inorganic platelets. TEM images showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Commercial Mg-Al LDH was modified with stearic acid and SDBS and compounded with PCL. 36 The addition of both the modified LDHs did not impact the melting temperature of the PCL composites in a meaningful way. It did, however, change the crystallization of PCL.…”
Section: Crystallization Behaviormentioning
confidence: 90%
See 2 more Smart Citations
“…Commercial Mg-Al LDH was modified with stearic acid and SDBS and compounded with PCL. 36 The addition of both the modified LDHs did not impact the melting temperature of the PCL composites in a meaningful way. It did, however, change the crystallization of PCL.…”
Section: Crystallization Behaviormentioning
confidence: 90%
“…Clearly, through the addition of LDH, one can modify the properties of the composite material when compared to the parent polymer. 36 The measured crystallization and melting enthalpies of both SBDS and stearic acid modified Co-Al LDH/LDPE composites decreased with an increase in filler content, indicating reduction of LDPE chain mobility, which in turn hinders the formation of polymer crystal domains. This supports XRD findings that indicated good interaction between the LDH particles and matrix, leading to delamination/exfoliation.…”
Section: Crystallization Behaviormentioning
confidence: 94%
See 1 more Smart Citation
“…Generally LDHs based polymer composites are prepared by three main techniques that is melt blending, solution intercalation and in situ polymerization. LDH‐PCL composites have specifically been prepared by high energy ball milling (HEBM), melt‐blending, and electrospinning . Research to date has focused mainly on LDH‐PCL composites for drug delivery aspects, morphology, and dispersion of systems .…”
Section: Introductionmentioning
confidence: 99%
“…LDH‐PCL composites have specifically been prepared by high energy ball milling (HEBM), melt‐blending, and electrospinning . Research to date has focused mainly on LDH‐PCL composites for drug delivery aspects, morphology, and dispersion of systems . Sorrentino et al reported mechanical properties (modulus, stress at yield point, strain at break point, and stress at break value) improvement in LDH‐PCL composite up to 2.8 wt %; however, the polymer suffered molecular weight reduction.…”
Section: Introductionmentioning
confidence: 99%